A scoping review on cancer and body image research - Jeong-Ju Yoo; Kenneth Carriveau; Angel Tran; Malay Shah; Mickey Langlais (Discover Psychology)
Abstract The purpose of this research is to explore previous studies that investigated the body image of cancer patients and survivors by identifying the variables that have been examined and the gaps in the current research through a scoping review. The researchers conducted extensive and methodical searches in several databases using relevant keywords. After analyzing the full text of 89 papers, 45 studies were included in this review, published between 1995 and 2024. Most of the studies were conducted solely with female participants, and breast cancer was the most commonly researched cancer type. The researchers identified variables that affect the body image perspectives of this population, with the surgery method being the most frequently tested variable, followed by education level, age, cancer state, and mental health. This scoping review highlights the need to pay particular attention to a vulnerable group of under-educated female cancer patients who must undergo invasive cancer treatment.